Wykorzystanie analizy scenariuszowej otoczenia w określeniu konkurencyjności sektora przedsiębiorstw przemysłu rolno-spożywczego - Firlej, Krzysztof (The Use of Scenario Analysis to Determine Competitiveness in the Food and the Agriculture Sector, 2006)
Delineates possible ways of applying scenario analysis techniques to assess competitiveness of companies in the food and the agriculture sector. The first theoretical part of the paper presents methodology of constructing a scenario of sector development and emphasize the role of scenario analysis in minimising risk in current and future business activity. The second part of the paper deals with practical use of the proposed analysis in the sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 228-236